Systemic lupus erythematosus impairs memory cognitive tests not affected by depression. (September 2014) - Calderón, J; Flores, P; Babul, M; Aguirre, JM; Slachevsky, A; Padilla, O; Scoriels, L; Henríquez, C; Cárcamo, C; Bravo-Zehnder, M; González, A; Massardo, L
Objective: Our aim was to assess the contribution of depression to cognitive impairment in patients with systemic lupus erythematosus (SLE). Methods: Clinical features, education, age, and Hospital Anxiety and Depression Scale (HADS) were evaluated in 82 patients with SLE and 22 healthy controls, all Chilean women. The Cambridge Neuropsychological Test Automated Battery (CANTAB eclipseTM) assessing attention, spatial memory, and learning and executive function domains was applied. Cognitive deficit definition: a cut-off for definite impairment was defined as a score below -2 standard deviations in at least one outcome measure in two or more domains. ANCOVA with stepwise selection evaluated influences of health status (SLE or control), age, education, and HADS depression and anxiety scores on cognitive outcomes. To avoid overfitting, a shrinkage method was performed. Also, adjusted p -values for multiple comparisons were obtained. Results: Cognitive deficit affected 16 (20%) patients, and no controls ( p  = 0.039). Median HADS depression score in SLE patients was 6 (range 0–19) and in controls was 0 (0–19), p  < 0.001). ANCOVA and shrinkage models showed that worse cognitive performance in sustained attention and spatial working memory tests was explained by the presence of SLE but not depression, whereas depression only affected a measure of executive function (I/ED Stages completed ). Conclusion: Depression has a limited role in cognitive impairment in SLE. Impairments in sustained attention and spatial working memory are distinctly influenced by yet-unknown disease-intrinsic factors.